English Learning Material for Journalism Courses: What are Students’ Needs? - Dewi, Resnita; Daud Rodi Palimbong; Roni La’biran; Reski Kambuno (UNIB Press, 2024)
This study aims to analyze student needs for learning materials for journalism courses at Indonesian Language and Literature Education, Toraja Indonesian Christian University. Using a qualitative approach, the study collected data through a series of in-depth interviews, surveys, and focus groups with students enrolled in journalism courses. The main objective of the study was to identify specific aspects of the learning material that students consider important, areas they find challenging, and suggestions for curriculum improvement. The results show that students value a combination of theoretical and practical learning, with particular emphasis on real-life case studies, multimedia skills, and the use of social media in journalism. Students also highlight the need for greater interaction with professional journalistic practitioners and field practice opportunities such as internships. Key difficulties students face include understanding journalistic investigative concepts, ethics, and legal aspects, as well as the development of technical skills such as writing, editing, and media analysis. This research suggests the need for a flexible and responsive curriculum that integrates the latest technology, provides teaching materials relevant to industry developments, and strengthens students' practical skills. These findings contribute to the development of more effective journalism teaching practices, which focus on preparing students for real challenges in the journalism industry.